2020
DOI: 10.3390/ijerph17155594
|View full text |Cite
|
Sign up to set email alerts
|

Women with Schizophrenia over the Life Span: Health Promotion, Treatment and Outcomes

Abstract: Women with schizophrenia show sex-specific health needs that differ according to stage of life. The aim of this narrative review is to resolve important questions concerning the treatment of women with schizophrenia at different periods of their life—paying special attention to reproductive and post-reproductive stages. Review results suggest that menstrual cycle-dependent treatments may be a useful option for many women and that recommendations re contraceptive options need always to be part of care provision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 80 publications
1
17
0
Order By: Relevance
“…The presence of estrogen at dopamine receptor sites in the brain helps to block the transmission of dopamine and the emergence of psychotic symptoms. Estrogen also regulates the activity of specific cytochrome P450 CYP enzymes that metabolize antipsychotic drugs, thus potentially increasing the levels of those metabolized by CYP1A2, e.g., clozapine and olanzapine [67].…”
Section: Antipsychotic Drug Response In Womenmentioning
confidence: 99%
“…The presence of estrogen at dopamine receptor sites in the brain helps to block the transmission of dopamine and the emergence of psychotic symptoms. Estrogen also regulates the activity of specific cytochrome P450 CYP enzymes that metabolize antipsychotic drugs, thus potentially increasing the levels of those metabolized by CYP1A2, e.g., clozapine and olanzapine [67].…”
Section: Antipsychotic Drug Response In Womenmentioning
confidence: 99%
“…For instance, using an animal model of psychosis (reversing disrupted latent inhibition), Arad and Weiner have shown that, in ovariectomized rats, co-administration of 17 beta-estradiol with haloperidol and clozapine increases the antipsychotic-like effect, particularly the effect on positive symptoms, as evaluated in animal models [ 8 ]. This suggests that the treatment of women with schizophrenia requires a post-reproductive stage focus that differs from that called for in standard treatment guidelines [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have described the relationship between estradiol levels and psychotic symptoms in other clinical conditions rather than schizophrenia [ 9 ]. These nosological entities have been called ‘the psychoses of the menstruation’ or menstrual psychoses, childbearing psychoses, or postpartum psychoses, and, in the case of psychoses at the time of menopause, the vast majority of authors have referred to them as postmenopausal psychoses [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations